Reconstruction nailing for ipsilateral femoral neck and shaft fractures - Tsarouhas, Alexandros (Springer Milan, 2011)
The surgical management of ipsilateral fractures of the femoral neck and shaft presents a difficult and challenging problem for the orthopaedic surgeon. The purpose of the present study was to report the mid-term results and complications in a series of patients who sustained ipsilateral femoral neck and shaft fractures and treated in our trauma department with a single reconstruction nail for both fractures. Eleven patients were included in the study with an average age of 46.4 years. The mean follow-up was 47 months (range, 15–75 months). There were no cases of a missed diagnosis at initial presentation. The mean time to union was 4.5 months for the neck fracture and 8.2 months for the shaft. There were no cases of avascular necrosis of the femoral head or non-union of the neck fracture. The mean Harris Hip Score was (85 ± 4.3). Complications included two cases of shaft fracture non-union and one case of peroneal nerve palsy. Heterotopic ossification at the tip of the greater trochanter was evident in two cases without causing any functional deficit. The current study suggests that reconstruction nailing produces satisfactory clinical and functional results in the mid-term. The complications involved only the femoral shaft fracture and were successfully treated with a single operative procedure.